SYNERGY OF FAMILY, SCHOOL AND COMMUNITY EDUCATION (Ontological and Epistimological Analysis) (IBTIKAR: Jurnal Studi Islam dan Sosial, 2024)
The community acts as the main source of knowledge and as "teachers" for learners. In addition to the community, the internet, libraries, and media also play significant roles. Education is acquired through social, cultural, and religious activities, and even negative activities such as criminality. Assessment is conducted informally through daily observation and interaction, with corrections and advice to ensure learners adhere to societal norms. Third, the synergy of family, school, and community education can be explained as follows: 1) Family, school, and community interact and share responsibilities in guiding and educating. Families support school education, schools create appropriate learning environments, and communities provide opportunities to apply knowledge. 2) These three educational entities share common goals, such as the development of good individuals, character formation, and preparation for societal contribution. 3)There is an understanding of the shared values and culture held by families, schools, and communities, including integrity, cooperation, and social responsibility.